Imagery in the Geguritan Undhaling Rasa anthology by Siti Sundari: A Stylistic Study - Eleiana Elva Rafidah (Raja Zulkarnain Education Foundation, 2026)
Geguritan is a modern Javanese literary work in the form of writing resulting from the expression of the author's feelings. The object of this research is the Geguritan Anthology